Private Unaided Engineering Colleges-Development and Future Directions - Karad, Vishwanath D. (Journal of Engineering Education Transformations, 1993)
The growth of any Nation is judged by the development of education specially in the field of Engineering Sciences and Technology. India is no exception to it. Prior to Independence, the facilities available in these fields were few and far from satisfactory. So was the case as regards industrial development. For example, the number of Engineering Colleges was only 8 which incresed to 78 in the year,1993.